An organelle-specific protein landscape identifies novel diseases and molecular mechanisms - Boldt, Karsten; Lu, Qianhao; Betts, Matthew J.; Russell, Robert B. (Nature Communications, 2016)
Mutations in proteins that localize to primary cilia cause devastating diseases, yet the primary cilium is a poorly understood organelle. Here the authors use interaction proteomics to identify a network of human ciliary proteins that provides new insights into several biological processes and diseases.
Gesehen am 14.05.2020